Evaluasi Kebijakan Penataan Organisasi Perangkat Daerah pada Pemerintah Kabupaten/Kota - Ani Heryani (Universitas Bandar Lampung (UBL), 2015)
Policy Evaluation of the structuring regional organization in the District / City Government carried out considering the enactment of Law No. 23 Year 2014 on Regional Government which brought the consequences of changing the authority of government affairs and district / city that needs to be done in the area of organizational structuring device Regency / City Government.Based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 67 Year 2011 on Guidelines for Institutional Evaluation explained that for the evaluation of regional institutional attention to three (3) dimensions of complexity that includes Differentiation Horizontal, Vertical Differentiation and Spatial Differentiation and Dimensions Dimensions Formalization and Centralization.Organization of the regional institutional arrangements should be made among others by the enactment of Law No. 5 of 2014 on State Civil Apparatus which requires the placement of employees in accordance with their competence as well as the rationalization of the number of employees per unit organizational needs through analysis of the workload.